化简:a^2+3a+2/a^2+6a+5=()/a+5
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 16:22:38
化简:a^2+3a+2/a^2+6a+5=()/a+5化简:a^2+3a+2/a^2+6a+5=()/a+5化简:a^2+3a+2/a^2+6a+5=()/a+5a^2+3a+2/a^2+6a+5=(
化简:a^2+3a+2/a^2+6a+5=()/a+5
化简:a^2+3a+2/a^2+6a+5=()/a+5
化简:a^2+3a+2/a^2+6a+5=()/a+5
a^2+3a+2/a^2+6a+5
=(a+2)(a+1)/(a+1)(a+5)
=(a+2)/(a+5)
(a^2+3a+2)/(a^2+6a+5)
=(a+1)(a+2)/(a+1)(a+5)
=(a+2)/(a+5)
化简:
a^2+3a+2/a^2+6a+5
=(a+2)/(a+5)
a^2+3a+2/a^2+6a+5
=[(a+2)(a+1)]/[(a+1)(a+5)]
=(a+2)/(a+5)
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
a-2a+3a-4a+5a-6a+...+99a-100a
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
a+a+1+a+2+a+3+a+4+a+5+a+6+a+7.+a+2013+a+2014=?
化简a+2a-3a-4q+5a+6a-7a-8a+...2001a+2002a-2003a-2004a
化简a-2a+3a-4a+5a-6a…+99a-100a
a-2a+3a-4a+5a-6a+7a-8a+9a-10a+11a.+99a-100a=
化简(a/a-2-a/a+3)*a^2+a-6/a
a=-1 求a-2a+3a-4a+5a-6a+...+99a-100a
化简(—a^3+3a^2-7a+5)+(5a^-6a)-(a^3-4a+7)
化简(—a^3+3a^2-7a+5)+(5a^-6a)-(a^3-4a+7)